Prevalence of Hypertension among adults aged 40 years and above in Ahiazu Mbaise, Imo State, Nigeria - CIC, Ebirim; OG, Udujih; UW, Dozie; CA, Agbaka; SM, Orji; CC, Anaele (Archives of Community Medicine and Public Health, 2018)
Introduction: This study was aimed at determining the prevalence of hypertension among adults aged 40 years and above in a rural Nigerian Population. Materials and Methods: Semi-structured questionnaires were completed by random selected rural dwellers. Aneroid sphygmomanometer was used to measure their blood pressure measurement. The mean of two separate blood pressure measurements was taken in each individual in a sitting position after about 5 minutes of rest. Data were analyzed using Statistical Package for Social Sciences computer software version 21.0 for windows. Total sample of 320 rural dwellers were recruited for the study. Result: The result indicated that 116 were males while 204 were females. The mean Systolic Blood Pressure (SBP) and Diastolic Blood Pressure (DBP) of participants were 138.5 ± 19.9mmHg and 80.6 ± 13.9mmHg respectively. The overall prevalence of hypertension in the population was found to be 51.3%. The prevalence of hypertension in this study is 56.9% in males and 48.0% in females. Conclusion: The finding of this study indicated need for specific interventions, focusing upon providing large scale population screening for hypertension and adequate blood pressure control to mitigate the mortality and morbidity associated with hypertension especially in the rural areas.